Spatial Gaps in Management Quality : Evidence from a Lagging Region in Croatia - Grover, Arti; Iacovone, Leonardo; Chakraborty, Pavel (World Bank, Washington, DC, 2020)
Embedding management and operational practices survey in a broader firm capabilities survey, this report finds that: (i) relative to the rest of Croatia, an average firm in the lagging region of the country (Eastern Croatia) is only slightly behind in the adoption of structured management practices. Nevertheless, overall, Croatia is farther from a frontier economy such as the United States. (ii) There is wide heterogeneity in adoption of management practices in the country, such that a large share of firms in the lagging region are badly managed relative to those in the rest of the country. (iii) Better managed firms in all regions, including Eastern Croatia, show superior firm performance. What drives better management? Global linkages matter for firms in other countries and in all regions of Croatia except the lagging region. Unlike other countries, firms in Croatia do not upgrade management quality as they age, perhaps due to lack of pro-competitive forces. This report recommends focusing on policies that improve allocative efficiency in the region and help firms establish global linkages, and more direct intervention for improving the management quality of firms.